A pluriatividade da agricultura familiar e a contribuição da renda rural para o crescimento do Produto Interno Bruto do estado de Roraima - Dias, José dos Santos (2016)
Agriculture is one of the most essential economic activities to Brazil. Therefore, the rural Brazil experienced profound changes related to modernization of the agricultural sector in recent decades. Brazil is considered an agricultural power by several factors: large territory with fertile areas, concentration of 12% of the world's fresh water, has a wide range of climates, among others. The Northern region of Brazil is the least part in the total volume of the agricultural sector, because it has low productivity rates compared with other regions. Its economy consists primarily of activities related to the primary sector, especially the extraction and agriculture. Roraima, as a member of the North, has an incipient agriculture in relation to other states of the federation, however, characterized mainly by the Family Agriculture, which represents 86.4% of farms. In the state of Roraima, family farming consists of small producers and represents the majority of farmers. Therefore, there is a need to identify each family activities has combined as a way to increase your income, or even as survival. This study sought to answer the following question: How is characterized pluriactivity Family Agriculture of the state of Roraima and how rural income contribution to the growth of Gross Domestic Product - GDP of the state of Roraima? In order to answer the research question, it sought to analyze the participation of agricultural and non-agricultural in income earned by family farming of the state of Roraima and to identify the contribution of these revenues to GDP growth in the state of Roraima, from the data collected by the National Sample Survey of Households in the period 2006-2013, and the Agricultural Census 2006. to be able to achieve the overall objective, we sought to: Scale the types of activities in the rural context in the state of Roraima, from 2006-2013; Identify and analyze the composition of the household income of rural areas of the state of Roraima; To analyze the evolution of all the incomes of rural households; Interpret the development of agricultural activities income, non-agricultural and other income of rural households Roraima; Identify and analyze the evolution of the State GDP growth; and identify and analyze the contribution of income from activities rural area of the state of Roraima in relation to the growth of state GDP. The main results were: the state of Roraima has a significant number of persons employed in a rural area, including having a greater representation to the country as a whole; family farming has a lower representation in number of establishments, but has 86.4% of farms in the state, higher than the national average (84.4%); the representativeness of agricultural activity within the state still takes the first place of busiest activity in the state; the average income of rural employee suffers little divergence from the income earned by urban employee; the income earned by the economically active population and the State GDP per capita have a positive correlation, and the income of the people in urban areas shows a greater impact on the State GDP than the income of people in rural areas of the state.